Research handbook on privacy and data protection law : values, norms and global politics / edited by Gloria González Fuster, Rosamunde Van Brakel, Paul De Hert. - González-Fuster, Gloria; Van Brakel, Rosamunde; De Hert, Paul (Research handbooks in information law., 2022)
An insightful overview of the key rules, concepts and tensions in privacy and data protection law. It highlights the increasing global significance of this area of law, illustrating the many complexities in the field through a blend of theoretical and empirical perspectives. Providing an excellent in-depth analysis of global privacy and data protection law, it explores multiple regional and national jurisdictions, bringing together interdisciplinary international contributions from Europe and beyond.